Atria in the Backpack, From Classroom to Convention: Reflections on the Conceptual Evolution of Higher Education as a Social Right - Paz Coronel, Daniela Patricia (Universidad Hemisferios, 2024)
This paper aims to conduct a descriptive analysis about the conceptual development that Chilean higher education has had from the perspective of Fernando Atria. We will use his texts;